E-3: GOVERNANCE AND ADMINISTRATION: THE EMERGENCE AND SCOPE OF WOMEN’S RIGHT TO ADEQUATE HEALTH IN AZAD JAMMU AND KASHMIR - Arif, Sardar M.A. Waqar Khan; Bannian, Bushra; Qurrahtulain, (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2023)
This paper focuses on governance and administration concerning the protection of women’s right to adequate health in Azad Jammu and Kashmir (AJK). In AJK, though the Government has initiated various projects and strategies for the protection of the right to health but there are certain challenges in their implementation. The Government of AJK is required to protect the right to health and improve the overall situation in the AJK. Women in AJK are vulnerable and are facing difficulties with the availability of health facilities. In this context, this paper analyses the government’s policies, strategies, and management towards the protection of women’s health. It discusses health situation available to women in AJK and highlights discrimination faced by them in public and private setups. The methodology used in this paper is analytical. The paper concludes that though the laws and policies of health are adequate but there are issues in the implementation. The argument developed throughout the article is that women in AJK need special attention to the protection of their health.